Asymmetric Causality Relationship between Oil Prices and Inflation in BRIC Countries - Syzdykova, Aziza; Abubakirova, Aktolkin; Kudabayeva, Lyazzat; Zhantayeva, Ardak; Omarova, Aizhan (International Journal of Energy Economics and Policy, 2022)
Sharp and persistent increases in oil prices continue to attract the attention of policy makers and economists, and many studies are conducted on the inflationary effects of oil price shocks. Knowledge of the inflationary effects of oil price increases will help monetary authorities adopt appropriate policies to meet these shocks. In this study, the asymmetric relationship between inflation rates and oil prices in the BRIC countries, which alone consumes approximately 28% of the world’s total oil consumption in 2020, has been examined. In this context, the relationship between the variables was investigated with the asymmetric causality analysis method developed by Hatemi-J and Roca (2014) using monthly data for the period January 2001 to September 2021. As a result of the analysis applied in the study, different results were obtained for the BRIC countries.